Planting methods and depths for the yacon (Smallanthus sonchifolius) crop - Quaresma, Mateus Augusto Lima; Oliveira, Fábio Luiz de; Amaral, José Francisco Teixeira do; Parajara, Magno do Carmo; Dalvi, Leandro Pin; Teixeira, Ariany das Graças (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Crop management is necessary in sprouting, cycle and productivity of most plants of commercial interest. However, recommendations and information are scarce for yacon cultivation, mainly regarding the possible interferences of planting method and depth in the crop development and production. Therefore, the objective was to study the influence of the planting methods and depths on yacon tuberous roots development and production in high altitude conditions. The experiment was a randomized complete block design, with four replications, in a subdivided plots scheme. The plots consisted of three planting methods (groove, pit and ridge) and subplots characterized by four planting depths (5, 10, 15, and 20 cm). Evaluations were carried out from the sprouting process of the rhizophores to the yield of tuberous roots. The planting methods in a pit and ridge had lower seedling mortality rates (27.5 and 20.2% lowers than grooves) and higher yields of tuberous roots (31.2 and 21.4% higher than grooves). The planting depths of 5 and 10 cm of the rhizophores were shown to be the most suitable for yacon cultivation for the three planting methods.